Cejogua Sports Corporation - Rendon, Elsa.; Macaspac, Glenn; Lavarias, Allan; Aguirre, Jason (Diliman, Quezon City College of Engineering, 2000)
The study focused on the Production System of Cejogua Sports Corporation. The Production System included the different processes, namely: cutting,sewing, printing and finishing. Using a stream diagnosis chart, major problems were identified, among which are 1) the improper distribution of workers among various sections, 2) the lack of implementation of the quota policy, 3) the idleness on the worker's part, and 4) the limited working area. Alternatives were generated as suggestions for the solution to these problems, and recommendations were arrived at. Suggestions (which correspond to each of the problems mentioned above), such as 1) the use of a forecasting technique to estimate future demand and capacity planning to determine capacity requirements, 2) the revision of the quota policy, so that the quota for piece rate workers will be in terms of output per day instead of the existing fixed=P 56.00 plus piece rate price times quantity formula, 3) the revision of the quota policy, so that workers have something to do for the most part of working hours, and 4) the "do nothing" alternative for the problem on work space were some of the solutions that the group proposed.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: Cejogua Sports Corporation; Sportswear industry; Production engineering